The Iron Age archaeology of the upper Thames and north Oxfordshire region, with especial reference to the eastern Cotswolds - Lang, A (2009)
This thesis considers the development of settlement landscapes in the Iron Age across two adjacent regions, the upland eastern Cotswolds and lowland upper Thames valley. Previous studies have focused on the differences in settlement form, economic practice and social development and therefore the possible dichotomy of heartland and hinterland landscapes. It is clear, however, that this is due to an imbalance of research brought about as a result of the natural landscape, interests of antiquarians and archaeologists and modern settlement focus and development. A new dataset of cropmark and geophysical survey material is presented as a way of redressing the imbalance. The focus within this study on banjo enclosures also provides an opportunity to analyse what remains a relatively enigmatic and understudied site-type that appeared during the Middle and Late Iron Age. The results illustrated and discussed here provide the chance to outline new narratives that take into account both practical and non-functional interpretations. From this, more is elucidated regarding these sites within the context of Middle and Late Iron Age settlement landscape developments. By integrating this new dataset within the wider context of the upper Thames and immediate environs a number of further and more general questions have been raised. These focus on the chronology of settlement development, the appearance and growth of exchange networks and the changing significance of open and enclosed settlements throughout the period. Differences have been used in the past to symbolise alternative social systems apparent across two settlement landscapes. However, as a result of the evidence presented here these perceptions are no longer viable as an interpretive framework. Instead, aspects of chronological development, settlement space and sphere of influence and interaction are discussed in relation to the evidence from Midlands and central southern Britain.